Promoting health in public schools: An experience report on the importance of healthy eating - Moliterno, Amanda; Silva, Thaynara Alexandra da; Meira, Matheus Zielinski Cavalheiro de; Furlan, Pedro Leocadio Lopes; Brito, Bárbara dos Santos; Campos, Mauricio Junior Giacomini; Inácio, Christian Schmitz; Santos, Aliny de Lima (Seven Editora, 2024)
The early stage of life plays a crucial role in the formation of healthy eating patterns, exerting a direct influence on children's cognitive and school performance. Health promotion strategies aimed at improving the quality of food have been shown to be effective in sensitizing women to the relevance of a balanced diet. The experience narrated shows that these initiatives have a significant impact, raising awareness of the issue and contributing to positive results in children's academic performance and well-being. DOI:https://doi.org/10.56238/sevened2024.001-047